A New Dynamic Mathematical Modeling Approach of Zero Waste Management System - Ashtashil V. Bhambulkar, Dr. Ranjit N. Patil (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Dr. Paul Palmer coined the phrase "zero waste" in 1973 to describe the complete removal of municipal solid waste (MSW) from landfills. Through a literature study and an interactive survey method, the conceptual basis and procedures employed in 25 cities throughout the world. The Battle Environment Evaluation System was used to study and analyse certain essential key issues involved in the present zero waste management system (BEES). The Delphi Technique was commonly utilised in this study to evaluate the present municipal solid waste management system (MSWMS) of the study area. The value of Environmental Quality (EQ) determined for the area under study's existing MSWM system was found to be 238; however, the ideal value for a good rating of an existing MSWM system should be 521. Various conclusions were drawn based on the facts and findings, including the development of innovative product design, a focus on the Solid Liquid Resource Management Centre (SLRMC), the Domestic Composting System (DCS), the design of optimal collection and transportation routes, the development of transfer stations, the implementation of the 3R principles, and the monitoring of the MSWM system at various stages. A model for zero-waste management has also been created and presented.